Cachexia: a problem of energetic inefficiency. Issue 4 (15th August 2014) - Argilés, Josep M.; Fontes-Oliveira, Cibely Cristine; Toledo, Miriam; López-Soriano, Francisco J.; Busquets, Sílvia
Abstract : An alteration of energy balance is the immediate cause of the so‐called cachexia. Although alterations of energy intake are often associated with cachexia, it has lately became clear that an increased energy expenditure is the main cause of wasting associated with different types of pathological conditions, such as cancer, infections or chronic heart failure among others. Different types of molecular mechanisms contribute to energy expenditure and, therefore, involuntary body weight loss; among them, adenosine triphosphate (ATP) consumption by sarcoplasmic reticulum Ca 2+ pumps could represent a key mechanism. In other cases, an increase in energy inefficiency will further contribute to energy imbalance.